Determinants of tax haven: overview of past studies - Jonathan, Jenson; Taofik Abidemi, Bello; Shiyanbade Najeemdeen, Iliyasu; Ismail Mohamed, Mohamed; Ugochukwu Anuforo, Peter (CSRC Publishing, 2018)
In recent years the issue of tax haven has been subjected under rigorous scrutiny by both the policymakers and regulatory authorities, due to the extent of the effects it has on both the developed nation (beneficial country) and particularly the developing nation which are the targeted tax haven territory. This study aimed at providing insight into the main determinants of tax haven and their effects. The method employed in this study involved reviewing prior study on tax haven. Findings suggests that the main determinants of tax haven region is not only the ones enshrined in Organization for Economic Co-operation and Development (OECD) criteria but others such governance index, institutional weakness, substantial amount of GDP from service industries etc. This study has also revealed that the conduit by which tax haven is being perpetrated is mainly via offshore financial centers (OFCs) which involve banks secrecy, transfer pricing (i.e. the devil in disguise) etc. This study recommends that stringent control measures and penalties for tax-resistant behaviors should be put in place by the international regulators like the World Bank and International Monetary Fund (IMF).